Mode of Adaptation of Coastal Dwellers: the Case of Bangladesh - Alam, Khursheed (2011)
Bangladesh is a disaster-prone country where every year it faces some cyclones, tidal bores, storm surges, etc. The present paper deals with the adaptability of coastal dwellers with particular reference to Bangladesh. In order to combat and survive from such catastrophes, coastal dwellers have to adapt differently in different situations. In this paper an attempt has been made to record their adaptation strategies in detail and to draw out some generalizations. The coastal dwellers‘ preparatory activities include taking shelter in cyclone shelters, strong houses, embankments, on trees, etc. Over the years, people and the agencies responsible for managing those disaster-effects learned a lot about the process of aversion or mitigation of such effects. People‘s approach, as it goes, is more for protection from rather than mitigation of the disasters‘ effect. People living in coastal areas are becoming increasingly aware about the risk of catastrophes and are better prepared to combat such situations. They need more preparatory supports from the government and non-governmental organizations (NGOs).